Comparative Analysis of Conventional Mortars and Instant Mortars (RAPI) Against Stone and Plastering Wall Pairs Judging from Quality, Cost, and Time - Girsang Hamonangan; Habibi T.B. Muhammad Nazmi (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2020)
The development of technology in construction has resulted in ready-made Mortar products is one product that is increasingly needed in the construction industry for several reasons such as material source, project location, quality accuracy, material efficiency, management and price factors. The larger the scale of the city and the more difficult to get quality materials at low prices and increasingly complex handling, it is enough to make an excuse in developing a more practical product with better quality assurance. The aim is to lead to ease in the process of work in the field while continuing to prioritize quality, but its utilization is still not maximized. This study tries to determine the neat instant mortar comparison with conventional mortar against the cost, quality, and time of the red brick and plastering wall pairs. The results showed that the compressive strength in 28 days the compressive strength of Mortar RM-115 with a compressive strength of 215.88 kg / cm2 which is larger and more measurable than Conventional Mortar with a value of 151.76 kg / cm2 whose implementation is sometimes incorrect. The time needed to complete the red brick wall pair work using Mortar RM-115 material is 14 days, while the time needed on the work of the red brick wall pair Conventional Mortar material is 15 days. So that the work of the red brick wall pair using the Mortar RM-115 material is more efficient 1 day and cleaner storage compared to using conventional Mortar material. The price of installing red brick walls with Mortar RM-115 materials in Bintaro Sector 7 housing is Rp. 36,858,425.99. While the price of installing red brick walls and plastering using conventional Mortar materials in Bintaro Sector 7 housing is Rp. 47,188,780.22. Work Installation of red brick walls and plaster using Mortar materials RM-115 is more expensive with a difference of Rp. 10,330,354.23.